ASSESSMENT OF FINANCIAL MANAGEMENT STRATEGIES AND CHALLENGES FACED BY FOOD SERVICE INDUSTRIES IN NSUKKA URBAN - UMENNUIHE, CHIDIOGO LOVELYN; NWACHUKWU, OKOROIGWE, CHINYERE; ASOGWA, OLIVIA AMAKA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study assessed the financial management strategies adopted by food service industries and the challenges they face in Nsukka Urban, Enugu State, Nigeria. A descriptive-comparative research design was employed to answer three research questions based on data collected from a sample of 250 food service industry staff. Two null hypotheses were tested at p < 0.05 level of significance. A structured questionnaire, validated by three experts with a reliability index of 0.79, was used for data collection. Descriptive statistics such as mean and standard deviation were used to analyse the data on the research questions while ANOVA was used to test the hypotheses. Findings revealed that the key financial management strategies adopted by the food service industry included cost management, revenue enhancement, budgeting and risk management. However, investment strategies like technology adoption and securing loans were not prioritised. Major challenges they faced were rising costs of raw materials, lack of access to loan facilities, lack of skilled labour, improper money management and fluctuating prices. The solutions to these challenges included improving energy efficiency, use of technology, monitoring cash flows and employee training among other things. The study concludes that the adoption of specific financial management strategy is dependent on the type of food service industry and their profit margins are influenced by the challenges they faced. Recommendations include prioritising energy-efficient practices, leveraging technology for invoicing, and fostering employee development. Policymakers should also facilitate access to loans and training programs to enhance sector resilience. These insights offer practical value to business owners, researchers, and stakeholders in optimising financial sustainability within Nigeria’s food service industry.